2012
DOI: 10.1093/mnras/sts372
|View full text |Cite
|
Sign up to set email alerts
|

Stratification, superfluidity and magnetar QPOs

Abstract: The violent giant flares of magnetars excite QPOs which persist for hundreds of seconds, as seen in the X-ray tail following the initial burst. Recent studies, based on single-fluid barotropic magnetar models, have suggested that the lower-frequency QPOs correspond to magneto-elastic oscillations of the star. The higher frequencies, however -in particular the strong 625 Hz peak -have proved harder to explain, except as high mode multipoles. In this work we study the time evolutions of nonaxisymmetric oscillati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 44 publications
2
47
0
Order By: Relevance
“…Taking into account effects associated with superfluidity may also be the answer. Superfluidity can move the continua such that damping is reduced (van Hoven & Levin 2008;Andersson et al 2009;Passamonti & Lander 2013) and may result in resonances between crust and core that could prolong mode lifetimes (Gabler et al 2013;Passamonti & Lander 2013). In fact, in their axisymmetric model Gabler et al (2013) found an oscillation at ∼600 Hz; however, this work did not demonstrate numerical convergence of this result.…”
Section: Introductionmentioning
confidence: 69%
“…Taking into account effects associated with superfluidity may also be the answer. Superfluidity can move the continua such that damping is reduced (van Hoven & Levin 2008;Andersson et al 2009;Passamonti & Lander 2013) and may result in resonances between crust and core that could prolong mode lifetimes (Gabler et al 2013;Passamonti & Lander 2013). In fact, in their axisymmetric model Gabler et al (2013) found an oscillation at ∼600 Hz; however, this work did not demonstrate numerical convergence of this result.…”
Section: Introductionmentioning
confidence: 69%
“…However, to us it seems hard to explain why only these particular overtones should be excited and not many more. A possible explanation was first presented in Gabler et al (2013b) and was confirmed by Passamonti & Lander (2013). Both groups find a preferential excitation of only a few particular high Alfvén overtones in the core: Let the crust be initially perturbed by a deformation with spatial structure corresponding to the eigenfunction of a crustal shear mode (as may happen during a giant flare).…”
Section: High-frequency Qposmentioning
confidence: 85%
“…(Braithwaite and Spruit 2004a;Braithwaite and Nordlund 2006b;Akgün et al 2013;Ciolfi and Rezzolla 2013;Gourgouliatos et al 2013;Lander and Jones 2012;Mitchell et al 2013;Passamonti and Lander 2013). A comprehensive review lies outside the scope of this chapter; we simply mention a few highlights.…”
Section: Generation Physicsmentioning
confidence: 99%